Sanger whistle-blowers dispute findings that cleared management of bullying. (15th November 2018) - Else, Holly
Current and former employees say investigation at the Wellcome Sanger Institute was flawed; the genomics powerhouse stands by the findings. Current and former employees say investigation at the Wellcome Sanger Institute was flawed; the genomics powerhouse stands by the findings.